Energy-Efficient Office Renovation: Developing design principles based on user-focused evaluation - KWON, Minyoung (A+BE | Architecture and the Built Environment, 2020)
This research aims to develop user-focused design principles for energy-efficient office renovations. The goal of this is to improve the quality and comfort of workspaces without compromising on energy-saving goals. Due to increasing sustainability requirements, new ways of working and changing office user preferences, there is a growing need for office renovations that not only deal with the energy performance and the replacement of building facilities, but also the occupants’ health and well-being. The renovation of office buildings can substantially reduce energy demand and improve building performance. For this reason, most studies regarding office renovations have focused on achieving better energy performance and indoor environmental quality. Also, several studies have investigated employee satisfaction in the work environment. However, the users are only considered after the buildings have been built and taken into use (e.g., postoccupancy evaluation), but not in the early stage of the design phase. Although there are building regulations and norms regarding indoor comfort, no clear design principles or guidelines considering users have been developed for office renovations. Therefore, it is necessary to explore how office users can be included in the early design stage of office renovations to improve their comfort and satisfaction. This led to the following main research question to be answered in this thesis: How can design principles for energy efficient office renovation be developed, based on the evaluation of user satisfaction? To answer to this question, field studies were conducted in 5 office buildings in the Netherlands. The cases consist of four renovated offices and one non-renovated office, originally built in 1960s to 70s. Before conducting empirical studies, a literature was conducted that is implemented in the theoretical framework. Ten parameters for satisfaction, such as thermal comfort, air quality, light, noise, personal control, privacy, concentration, communication, social contact, and territoriality, were defined and were classified based on the findings from 124 items of studies focussing on physical and psychological satisfaction in the work environment. Each chapter and several sub-research questions address these parameters. Based on the findings, a classification of user satisfaction parameters is proposed, including a discussion about an hierarchy of ten parameters. This hierarchy is structured based on theoretical definitions of parameters and its physical, functional, and psychological influences. For the empirical studies, a multidisciplinary methodology was applied to prioritise the important aspects of office renovations. The various methods for data collection and analyses included examining energy use and the quality of indoor climate after renovation, and investigating the impact of design factors on user satisfaction with thermal, visual, and psychological comfort. The design factors in this research are influential design factors on user satisfaction. These are office layout, orientation, window-to-wall ratio, and desk location. The empirical studies are structured in four parts. Energy consumption As a preliminary study, architects and facility managers were interviewed to identify the building characteristics of renovated offices and energy consumption. Henceforth, the five case studies were conducted. A cross-case-analysis was used to compare the building characteristics of the five case studies. The energy consumption of renovated and non-renovated offices were compared by different energy matrix. In addition, the limitations that hinder the achievement of better energy performance, were described. Indoor climate and users’ thermal comfort Indoor temperature and humidity were measured by using data loggers to identify the condition of the indoor climate for users’ thermal comfort after renovation. A questionnaire, including thermal sensation, preference, and satisfaction, was distributed among the building users. The monitored climate data of the thermal conditions were evaluated based on the Dutch building norms and users’ responses. Personal control This part aims to identify the relationship between the degree of personal control over indoor environmental conditions (e.g., temperature, ventilation, light) and user satisfaction with thermal and visual comfort. This study investigated the impact of personal control on user satisfaction through user surveys and statistical analyses. The results present that higher controllability leads to more satisfaction in terms of thermal and visual comfort. It also reveals the psychological impact of personal control on user satisfaction by showing differences in perceived satisfaction according to ‘no control’ and ‘do not have’. These findings provide support to workplace management and the design of personal environmental control systems. User satisfaction with thermal, visual, and psychological comfort Together with the indoor climate conditions of workspaces, 579 office users from the five cases were studied. The responses of the users were collected and analysed through statistical analyses. This study phase demonstrates the results of the impact of influential office design factors on user satisfaction with thermal, visual, and psychological comfort. It also contributes to predicting which design variables may bring better user satisfaction. After the empirical studies, the conceptual study was conducted through energy simulation to evaluate the impact of the combination of design factors on the energy demand. Twenty-four office model variants were created based on the combination of design factors, which are consisted of 3 or 4 variables. The energy demand is predicted according to the office model variants. As a next step, the design principles were developed by incorporating the previous findings and various perspectives of energy-efficient office renovation. An overview of the predicted user satisfaction and energy demand is graphically provided in this research. Based hereupon, a flow chart is created for applying the principles to the renovation process. First, the most influential design factors on thermal, visual, and psychological satisfaction are suggested in the design principles. Next, the values of predicted user satisfaction and energy demand can be evaluated by following the flow chart, to find the optimal renovation plan. In this step renovation alternatives are suggested in terms of office variants to create a balance between user satisfaction and energy efficiency. Last, if design limitations occur, the degree of personal control should be included to increase user satisfaction. The comprehensive design principles can help architects, designers, and facility managers to make design decisions in an early stage of office renovations. To summarise, this research demonstrates the relationship between design factors, indoor climate and user satisfaction, without neglecting the fundamental goal of office renovation: reducing the energy demand, upgrading facilities, and improving building performance. It also contributes to developing design principles for office renovations with integrated user perspectives, that improve users’ satisfaction and comfort, as well as energy efficiency. Although users’ individual control over the indoor environment has a significant impact on satisfaction, it needs to be explored further. In addition, it is important to mention that other variables such as building elements and various façade configurations need to be included in further research. In conclusion, design principles considering both energy efficiency and user satisfaction will not only contribute to an increase in the value of a building, but also serve as a stepping stone for user-focused office designs or user-related aspects of the built environment.